A real-time simulation platform for maximum power point tracking algorithm study in solar photovoltaic system - Meng Chung, Tiong; Hamdan, Daniyal; Mohd Herwan, Sulaiman; Mohd Shafie, Bakar; Suliana, Ab Ghani (Arqii Publication, 2019)
This paper presents the application of controller hardware-in-the-loop (C-HIL) for real-time study of maximum power point tracking (MPPT) algorithm in solar photovoltaic (PV) system. The testing platform in this study which consist of three series connected PV modules together with a DC/DC boost converter were modelled and implemented using Tyhoon HIL-402. For the MPPT controller, a conventional perturb and observe (P&O) and a well-established particle swarm optimization (PSO) based MPPT algorithm are developed and implemented in a digital signal processor. The performance of both algorithms were examined under real-time working condition with 10 different partial shaded test cases. From the study, the P&O shows a faster convergence speed which it can track for maximum power point rapidly up to 0.5070 s compared to the fastest tracking of PSO at 1.3598 s. However, PSO shows a greater capability in tracking for true maximum power point under partial shaded conditions with average output efficiency up to 99.92% compared to P&O which is only 76.76%.